Strategi Penanganan Covid-19 Di Kota Pekalongan - Kuat Ismanto; Sobrotul Imtikhanah; Choliq Sabana; Hartati Hartati; Projo Angkasa (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2022)
This paper aims to analyze the effectiveness of handling Covid-19 in Pekalongan City. The primary data of this research was obtained through focus group discussions (FGD) with the Covid-19 implementing officers in Pekalongan City and also the community. The data obtained were analyzed descriptively and qualitatively. The results of this study indicate that the handling of COVID-19 is categorized as successful, which is indicated by increased recovery and decreased mortality. For this reason, recommendations are formulated for local governments: 1) Consistency in compliance of the Task Force and OPD with Central Government regulations; 2) Strengthening coordination between the Task Force and OPD within the local government environment; 3) Accurate and effective delivery of education about Covid-19; 4) Enforcement of Perwal and general public compliance with Covid-19 health protocols; 5) Maximizing the role of religious leaders (ulama) in handling Covid-19; 6) Strengthening the community's economy during the pandemic through local government coordination. Keywords: Covid-19, treatment effectiveness, Covid-19 task force, health protocol